THE ROLE OF CORPORATE CULTURE IN FORMING THE PROFESSIONAL COMPETENCE OF FUTURE OFFICERS (Physical Culture and Sport: Scientific Perspective, 2024)
The purpose of the article is to highlight the role of corporate culture in the structure of professional competence of future officers. To achieve the goal, a set of general scientific methods of cognition were used, in particular: analysis of scientific literature, generalization, synthesis, comparison. Research results. The article reveals the role of corporate culture in the formation of professional competence of future officers. Its significant potential as a component of military professionalism and as a continuum for the development of cadets' professional competencies is emphasized. The formation of professional competence of future officers is not limited to receiving a military education, but correlates with the entire structure of military-professional activity in which the cadet participates, the specifics of the professional environment in which he is immersed, professional relations in which he "joins". Given the complexity of the professional tasks of future officers, it is appropriate to consider corporate culture in the structure of their professional competence as a systemic quality that characterizes the level of social and professional development of a cadet, the way of realizing his professional potential in the process of performing professional tasks. It was established that corporate culture plays a dual role in shaping the professional competence of future officers. On the one hand, it is a component of the professional profile of a new generation serviceman. On the other hand, it is an environment for the development of cadets, which models the values, ideals, norms, and rules of military professional activity in real conditions. Immersion of cadets in the corporate environment of a military educational institution enables them to master corporate ethics, the basics of communication in military-professional activities, to enrich knowledge about hierarchical relationships, etc.Various didactic tools are used to use the corporate capabilities of military educational institutions in the formation of professional competence of future officers. Taking into account the corporate features of military education and military-professional activity within the educational and training and educational process contributes to the development of the subject position of future officers: initiative and activity as the desire of future officers to go beyond formal interaction, to deepen and expand their education through versatile participation in educational work; independence as the ability of future officers to take independent, proactive actions within the framework established by military education; readiness for responsibility and the choice of effective strategies of professional activity, conscious behavior and actions, etc. Using the potential of the educational environment in this context will make it possible to intensify the process of forming the professional competence of future officers, because it will provide cadets with a set of necessary roles and technologies for their practical implementation.
Keywords: professional competence; future officers; corporate culture; cadets; innovative technologies; training; military educational institutions